KOMPARASI ANALISIS SWOT DAN SPACE DALAM MENETAPKAN STRATEGI BISNIS BERDASARKAN KONDISI LINGKUNGAN PERUSAHAAN PADA PERUSAHAAN OUTSOURCING - Melati Diyani Putri; Marbudyo Tyas Widodo (Jurnal Riset Manajemen dan Bisnis, 2015)
This research was conducted to compare SWOT and SPACE analysis in setting business strategy and formulate an appropriate functional strategy for corporations based on the internal and external environment of the company. The necessary data in this study were obtained through the dissemination of questionnaires, in-depth interviews, and observations directly to the company then analyzed using the case study method. The results in this study indicate that the alternative strategy of SWOT analysis is better to apply for the company than the analysis of SPACE. Then using QSPM matrix that retrieved the most appropriate business strategies for companies based on their environment is an extension of the market both in the geographic or demographic.Key words : Business strategy, SWOT and SPACE analysis, Outsourcing companies